Factors that influence behaviour intention of UiTM Shah Alam students in purchasing eco-friendly product / Norsyahira Syahid Tay - Syahid Tay, Norsyahira (2019)
The level of awareness and knowledge of Malaysian on green technology including the aspects of eco-friendly products was still at the low level. Thus, this study explored the factors that influence behaviour intention of UiTM Shah Alam undergraduate students in purchasing the eco-friendly product since they are part of young generation consumer. The factors of environmental concern, attitude, eco-friendly product knowledge, price and policy used as the influence factors for behaviour intention of purchasing the eco-friendly product among UiTM Shah Alam students. Cross-sectional survey used as data collection to answer the research objective. There are 392 students from 14 faculties in UiTM Shah Alam as the sample size for this study. Stratified random sampling used as sampling technique. This study also used primary data collection by using questionnaire distributed to undergraduate students of UiTM Shah Alam. The data analyzed by using SPSS Statistical. The result shows there is high level of behaviour intention among UiTM Shah Alam students in purchasing the eco-friendly product. There is significant relationship between environmental concern, attitude, eco-friendly product knowledge, price and policy with behaviour intention of UiTM Shah Alam student in purchasing eco-friendly product too. In addition, the main factor that influencing behaviour intention among UiTM Shah Alam students is environmental concern.